The Reality of the Legislative Intent in Requiring a Grievance to Be an Alternative or Prelude Means to Administrative Litigation - Ahmed, Mohammed Sulaiman Al (Journal of Legal and Political Studies, 2015)
The laws which regulate administrative judiciary requires before rising a case an administrative appeal and this is a a procedure by which the person who is administration contender to apply the request to shows his objection on the administrative procedure which is unfair for him based on reasons presented trying to persuade the applicant has requested the grievance to reverse its decision. The is doubt that this condition based on legislative policy which make the fact of legislative intent for require it, that our administrative judiciary did not judgment in Iraq generally and in Kurdistan region specially to disclose it and this leads to loss the legislative policy for its requirement and away from the right way to enforcement it so this caused a loss of a lot of rights instead of get it. We will try here to follow the fact of legislative intent for requirement administrative appeal as prefatory way to rise a case against the administration or as alternative dispute resolution, to find the role of administrative appeal will help to change understanding its meaning also change judiciary decisions by search of negative points of legislative requirement of administrative appeal through administrative judiciary theories in Iraq and Kurdistan region.
Keywords: administrative judiciary; Objection; persuade; appeal